Angiographic features and progression risk factors in children with asymptomatic moyamoya disease - Wang, Jiyuan; Zhang, Qian; Di, Fei; Zhang, Dong (Frontiers in Neurology, 2024)
ObjectiveThis study aims to explore the potential contribution of angiographic characteristics in the increased stroke risk among pediatric patients.MethodsThis study retrospectively enrolled pediatric patients with ischemic, hemorrhagic, and asymptomatic moyamoya disease. Their hemispheres were categorized into five groups for the analysis of angiographic characteristics, which included Suzuki’s stage, moyamoya vessels, lenticulostriate artery, thalamotuberal artery, thalamoperforating artery, anterior choroidal arteries, posterior choroidal arteries, and posterior cerebral artery involvement.ResultsTwo hundred and nineteen pediatric patients with four hundred and thirty-eight hemispheres were enrolled. There was no significant difference in collateral dilatation between asymptomatic and hemorrhagic hemispheres. However, asymptomatic hemispheres had significantly lower incidence of posterior cerebral artery involvement and Suzuki’s stage compared to hemorrhagic (p = 0.008, p = 0.004) and ischemic hemispheres (p = 0.026, p < 0.001). Multivariate analysis revealed that Suzuki’s stage (p = 0.002, 95% CI 1.261–2.867) is a risk factor for ischemia, while age (p < 0.001, 95% CI 0.712–2.014) and posterior cerebral artery involvement (p = 0.037, 95% CI 0.087–13.377) are risk factors for hemorrhage.InterpretationAngiographic features in children with asymptomatic moyamoya disease resemble those observed in the hemorrhagic pediatric patients, indicating that greater attention should be focused on the risk of future hemorrhage in these patients, rather than on ischemia. Additionally, studies have demonstrated a correlation between posterior cerebral artery involvement and age with the incidence of hemorrhage. Monitoring angiographic characteristics may assist in tracking the transition from asymptomatic to symptomatic hemispheres.